bearing in mind that standard form for a linear equation means
• all coefficients must be integers, no fractions
• only the constant on the right-hand-side
• all variables on the left-hand-side, sorted
• "x" must not have a negative coefficient
![\bf (\stackrel{x_1}{-4}~,~\stackrel{y_1}{-1})\qquad (\stackrel{x_2}{\frac{1}{2}}~,~\stackrel{y_2}{3}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{3}-\stackrel{y1}{(-1)}}}{\underset{run} {\underset{x_2}{\frac{1}{2}}-\underset{x_1}{(-4)}}}\implies \cfrac{3+1}{\frac{1}{2}+4}\implies \cfrac{4}{~~\frac{9}{2}~~}\implies \cfrac{4}{1}\cdot \cfrac{2}{9}\implies \cfrac{8}{9}](https://tex.z-dn.net/?f=%5Cbf%20%28%5Cstackrel%7Bx_1%7D%7B-4%7D~%2C~%5Cstackrel%7By_1%7D%7B-1%7D%29%5Cqquad%20%28%5Cstackrel%7Bx_2%7D%7B%5Cfrac%7B1%7D%7B2%7D%7D~%2C~%5Cstackrel%7By_2%7D%7B3%7D%29%20%5C%5C%5C%5C%5C%5C%20%5Cstackrel%7Bslope%7D%7Bm%7D%5Cimplies%20%5Ccfrac%7B%5Cstackrel%7Brise%7D%20%7B%5Cstackrel%7By_2%7D%7B3%7D-%5Cstackrel%7By1%7D%7B%28-1%29%7D%7D%7D%7B%5Cunderset%7Brun%7D%20%7B%5Cunderset%7Bx_2%7D%7B%5Cfrac%7B1%7D%7B2%7D%7D-%5Cunderset%7Bx_1%7D%7B%28-4%29%7D%7D%7D%5Cimplies%20%5Ccfrac%7B3%2B1%7D%7B%5Cfrac%7B1%7D%7B2%7D%2B4%7D%5Cimplies%20%5Ccfrac%7B4%7D%7B~~%5Cfrac%7B9%7D%7B2%7D~~%7D%5Cimplies%20%5Ccfrac%7B4%7D%7B1%7D%5Ccdot%20%5Ccfrac%7B2%7D%7B9%7D%5Cimplies%20%5Ccfrac%7B8%7D%7B9%7D)
![\bf \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-1)}=\stackrel{m}{\cfrac{8}{9}}[x-\stackrel{x_1}{(-4)}]\implies y+1=\cfrac{8}{9}(x+4) \\\\\\ \stackrel{\textit{multiplying both sides by }\stackrel{LCD}{9}}{9(y+1)=9\left( \cfrac{8}{9}(x+4) \right)}\implies 9y+9=8(x+4)\implies 9y+9=8x+32 \\\\\\ 9y=8x+23\implies -8x+9y=23\implies 8x-9y=-23](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Barray%7D%7B%7Cc%7Cll%7D%20%5Ccline%7B1-1%7D%20%5Ctextit%7Bpoint-slope%20form%7D%5C%5C%20%5Ccline%7B1-1%7D%20%5C%5C%20y-y_1%3Dm%28x-x_1%29%20%5C%5C%5C%5C%20%5Ccline%7B1-1%7D%20%5Cend%7Barray%7D%5Cimplies%20y-%5Cstackrel%7By_1%7D%7B%28-1%29%7D%3D%5Cstackrel%7Bm%7D%7B%5Ccfrac%7B8%7D%7B9%7D%7D%5Bx-%5Cstackrel%7Bx_1%7D%7B%28-4%29%7D%5D%5Cimplies%20y%2B1%3D%5Ccfrac%7B8%7D%7B9%7D%28x%2B4%29%20%5C%5C%5C%5C%5C%5C%20%5Cstackrel%7B%5Ctextit%7Bmultiplying%20both%20sides%20by%20%7D%5Cstackrel%7BLCD%7D%7B9%7D%7D%7B9%28y%2B1%29%3D9%5Cleft%28%20%5Ccfrac%7B8%7D%7B9%7D%28x%2B4%29%20%5Cright%29%7D%5Cimplies%209y%2B9%3D8%28x%2B4%29%5Cimplies%209y%2B9%3D8x%2B32%20%5C%5C%5C%5C%5C%5C%209y%3D8x%2B23%5Cimplies%20-8x%2B9y%3D23%5Cimplies%208x-9y%3D-23)
Answer:
188 ft
Step-by-step explanation:
helicopter
___________________________________________
|\ 54°
| \
| \ 320 ft
| \
| 54° \
-------------+--------------+-------------------------------
x
cos 54° = x/(320 ft)
x = 320 ft × cos 54°
x = 188 ft
Answer: 188 ft
The answer to this question of yours is B
<span>As x approaches positive infinity, f(x) approaches negative infinity, since the graph goes down</span>
This is the expression simplified: